Competitive Intelligence Advantage: How to Minimize Risk, Avoid Surprises, and Grow Your Business in a Changing World (Wiley) - Sharp, Seena (Journal of Sustainable Competitive Intelligence, 2012)
A practical introduction to the necessity of competitive intelligence for smarter business decisions-from a leading CI expert and speaker In Competitive Intelligence Advantage, Seena Sharp, founder of one of the first Competitive Intelligence firms in the US, provides her expert analysis on the issues and benefits of CI for today's businesses. CI is critical for making smarter business decisions and reducing risks when formulating strategies, leading to more profits and fewer mistakes. This is a practical guide that explains what CI is, why data is not intelligence, why competitor intelligence is a weak sibling to competitive intelligence, when to use it, how to find the most useful information and turn it into actual intelligence, and how to present findings in the most convincing manner. Importantly, Sharp argues that businesses would benefit from shifting their perspective on CI from viewing it as a cost to viewing it as an investment that saves money and provides immediate value. Author Seena Sharp is a noted CI expert who established Sharp Market Intelligence in 1979 Addresses all the most common myths and misconceptions about CI Includes more than sixty examples of when to use CI Completely explains the ins and outs of CI, and why your company will act faster and more aggressively with CI Competitive intelligence is a management tool that is misunderstood and underestimated, yet results in numerous benefits. If you are a senior level executive or operate a business-and you aren't tapping the power of CI to improve your decision making-you are missing a potent advantage. Book Description Publication Date: October 19, 2009 | Series: Wiley Clique Aqui